The cost of child and adolescent injuries and the savings from prevention - Miller, Ted; Finkelstein, Eric; Zaloshnja, E; Hendrie, Delia (American Public Health Association, 2012)
Cost-of-illness data are useful in comparing magnitudes of various health problems, assessing risks, setting research priorities, and selecting interventions that most efficiently reduce health burdens. With analyses of national and state data sets, this chapter presents data on the frequency, costs, and quality-of-life losses associated with child and adolescent injury in 2000. The frequency, severity, and costs of injury—unintentional and intentional—make it a leading child and adolescent health problem. Child and adolescent injuries in 2000 resulted in an estimated $24 billion in lifetime medical spending and $82 billion in present and future work losses, including caregiver losses. These injuries killed approximately 18,000 children and left approximately 160,000 children and adolescents with permanent work-related disabilities. Because Medicaid and other government sources paid for 29% of the days children spent in hospitals because of injury, the government has a financial interest in, and arguably a responsibility for, ensuring the safety of disadvantaged children.Many proven child safety interventions cost less than the medical and other resource costs they save. Thus, governments, managed care companies, and third-party payers could save money by increasing the routine use of selected child safety measures, such as functional family therapy for juvenile offenders, booster seats, bicycle helmets, smoke alarms, and graduated driver licensing. Yet these and other proven injury prevention interventions are not universally implemented. Possible barriers to adoption include the following: (1) savings may be split across multiple payers, (2) the payback period may be too long, (3) safety device subsidizers would have to subsidize parents who would buy the devices anyway as well as parents who would not, and (4) intervention may be a risky departure from proven practice or prove politically difficult.